2019
DOI: 10.1186/s41239-019-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between college students’ writing anxiety and the pedagogical use of online resources

Abstract: This study reports on how the use of online resources based on systemic functional linguistics (SFL) impacted college students' emotional alignment with writing practices. Through qualitative analyses of in-class discussions, students' interviews and reflections, as well as their written pieces gathered in a Chinese university, the case study shows that the students were able to overcome their fears with writing construction associated with their dearth of effective knowledge, albeit through a zigzag trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The highest mean is for the situation which evokes writing anxiety is 'afraid of writing test' (3.57), followed by situations 'worry about receiving negative comments & evaluation ' (3.27). This is similar to the study of Zhang (2019), which also found that 87% of 2nd-year student's reveal was found to be afraid of writing tests. Figure 10 reports the mean for writing anxiety causal factor 2: Negative Writing Attitude.…”
Section: Findings From Survey Questionnaire (Cwai) For Causes Of Writing Anxiety 431 Mean For Negative Writing Experiencesupporting
confidence: 88%
See 1 more Smart Citation
“…The highest mean is for the situation which evokes writing anxiety is 'afraid of writing test' (3.57), followed by situations 'worry about receiving negative comments & evaluation ' (3.27). This is similar to the study of Zhang (2019), which also found that 87% of 2nd-year student's reveal was found to be afraid of writing tests. Figure 10 reports the mean for writing anxiety causal factor 2: Negative Writing Attitude.…”
Section: Findings From Survey Questionnaire (Cwai) For Causes Of Writing Anxiety 431 Mean For Negative Writing Experiencesupporting
confidence: 88%
“…Hence, when student writers are to produce their writing under an assessment context further aggravates their fear, they will start to experience mind blank syndrome and panicking feeling. (Zhang, 2019) These are signs of the appearance of anxiety when the time given was not enough for them to complete the writing task which raises the chance for student writers to commit more writing mistakes resulting in poor writing performance (Alfiansyah et al, 2017). c. Linguistic difficulty: Linguistic difficulties are a common problem often faced by foreign or second language writing.…”
Section: Causes Of Writing Anxietymentioning
confidence: 99%
“…Online resources also provide a rich-language support that can lower anxiety. A recent study carried out by Zhang (2019) revealed that the integration of the Systemic Functional Linguistics technique and online resources reduce students' anxiety and offer knowledge they need during the writing process.…”
Section: Making Use Of Online Videos and Academic Articles As Learnin...mentioning
confidence: 99%
“…In a recent study, teachers reduced foreign language anxiety by giving more practice time, providing scaffolding and giving individual instruction (Chuang, 2019). In the context of EFL writing courses, other scholars have done empirical studies to reduce students' writing anxiety such as using the writing process approach (Bayat, 2014), pre-writing (Schweiker-Marra & Marra, 2000, peer-feedback (Yastibas & Yastibas, 2015), and Systemic Functional Linguistics (SFL) and online resources (Zhang, 2019). Albeit many scholars have discussed both theoretical and practical findings in writing anxiety research, sparse attention is directed to exploring teachers' strategies in alleviating students' writing anxiety in higher education contexts.…”
mentioning
confidence: 99%
“…33 Following this approach, the results of research on FLA have been relatively uniform. 43 According to Brown, anxiety which can be a debilitative or facilitative factor plays a role in second or foreign language learning. 1 Debilitative anxiety is the negative kind that affects the performance of learners to some extent; several studies have revealed the negative linear relationship between learners' anxiety and their performance in language classes.…”
Section: Overview Of Foreign Language Anxietymentioning
confidence: 99%